Creating visible-to-near-infrared mechanoluminescence in mixed-anion compounds SrZn2S2O and SrZnSO. (February 2020) - Chen, Changjian; Zhuang, Yixi; Tu, Dong; Wang, Xiandi; Pan, Chaofeng; Xie, Rong-Jun
Abstract: Mechanoluminescence (ML) materials featuring light emission in response to mechanical stimulus have shown promising applications in damage diagnosis, dynamic force detection, and information storage. However, their applications are greatly limited by a very small number of available ML materials as well as unsatisfied ML spectra. In this paper, we developed novel ML materials with intense ML and super-broad visible-to-near-infrared (470–1600 nm) spectra by incorporating lanthanide ions or transition metals into mixed-anion compounds SrZn2 S2 O and SrZnSO. These mixed-anion compounds show a linear relationship between ML intensity and applied force, allowing them to be used in non-contact/multi-touch stress sensing. Moreover, the mixed-anion compounds exhibit multiband near-infrared ML enabling a significant bright-field stress sensing approach without the interference of ambient light. This work offers a unique insight for discovering new ML materials and enriching the ML spectral range, thereby promoting their potential applications in stress intelligent sensors, electronic skins, and human-machine interfaces. Graphical abstract: A new concept by incorporating lanthanide ions or transition metals into mixed-anion compounds to discover new mechanoluminescent materials and expend their spectral coverage is proposed. Examples in SnZn2 S2 O, SrZnSO, β -SiAlON, and SrSi2 O2 N2 showing excellent force-to-luminescence response, tunable wavelength from 470 to 1600 nm, and new stress-sensing applications are demonstrated. Image 1 Highlights: A new concept of discovering ML materials in mixed-anion compounds is proposed. Several new ML materials with excellent properties are discovered, enabling to cover an ultra-wide spectral range of 470–1600 nm. A world-record longest ML of 1534 nm is realized in the newly discovered ML material. A creative bright-field stress sensing approach based on NIR ML ( 1534 nm) and NIR detection is proposed.